Development, implementation and evaluation of an optimized cross-sectoral rehabilitation program after acute hip fracture surgery: A mixed-methods study. (April 2022) - Poulsen, Lise Kronborg; Ilvig, Pia Maria; Brendstrup, Louise; Rasmussen, Caroline Louise; Pedersen, Kirsten Aunskjaer; Ditlevsen, Peter; Henriksen, Sara Elizabeth; Kirk, Jeanette Wassar
Abstract: Fall-related hip fracture (HF) is a frequent trauma in Scandinavia with a yearly incidence of 8, 000 among ≥65-year-old citizens in Denmark. The rising incidence and global predictions are alarming since a HF is a major, and potentially fatal, trauma to the citizen, requiring acute surgery, a multimodal approach and post-operative crosssectoral rehabilitation. However, continuity of the rehabilitation program is frequently interrupted in the transition between sectors, compromising optimal recovery of frail citizens. Thus, there is a need to develop and implement optimized cross-sectoral rehabilitation after HF. The purpose of this explorative study was to develop, implement and evaluate an optimized cross-sectoral rehabilitation program (OCRP) after HF surgery using validated theoretical frameworks. OCRP was developed, implemented and evaluated in one municipality using a pragmatic user-centered approach, quantitative and qualitative data collection and theoretical frameworks including the Behavior Change Wheel (BCW) and RE-AIM. Results of OCRP showed optimized rehabilitation based on motivated health professionals, high patient satisfaction and tendencies of improved levels of physical function. No re-referrals to rehabilitation were reported after OCRP. The BCW, RE-AIM and user-centered approach to program development, implementation and evaluation are useful to apply in program development and evaluation processes across sectors, professions, and medical specialties. Highlights: Facility visits can optimize cross-sectoral collaboration in HF rehabilitation. RE-AIM framework can guide implementation and evaluation of HF rehabilitation. OT assessment can optimize target and content in rehabilitation after hip fracture. Inter-professional, cross-sectoral collaboration support adherence and maintenance. OCRP is recommended for public collaborators in rehabilitation of fragile patients.